Monitoring Data Center Cyber dengan Camera Network Fiber Optik - Sinaga, Dimpo (Universitas Dirgantara Marsekal Suryadarma, 2018)
In dealing with free trade there will be complex problems in the business world. One of the complex problems is the need for extensive information that can be useful for both internal and external parties. Especially in the field of server data rack rental business, because this business requires a lot of capital so it needs a computerized security system. The problem faced today is to facilitate the process of leasing server data racks and based on these problems. Networking is a set of computers that are connected by cable or wireless to other computers in order to communicate with each other, exchange information, share files and printers. The advantages of networking can produce information that is useful for the interests of internal and external parties.